The effect of prosody teaching on developing word recognition skills for interpreter trainees: An experimental study - Yenkimaleki, Mahmood; Heuven, Vincent J. van (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
The present study investigates the effect of the explicit teaching of prosodic features on developing word recognition skills with interpreter trainees. Two groups of student interpreters were composed. All were native speakers of Farsi who studied English translation and interpreting at the BA level at the State University of Arak, Iran. Participants were categorized into two groups at random, but with equal division between genders (9 female and 9 male students in each group). No significant differences in English language skills (TOEFL scores) could be established between the groups. Participants took a pretest of word recognition skill before starting the program. The control group received exercises in listening comprehension, while the experimental group spent part of the time on theoretical explanation and practical exercises developing conscious knowledge of prosodic features of English, such as word stress. The total instruction time was the same for both groups, i.e. 8 hours. Students then took a posttest of word recognition skills. The results show that prosodic feature awareness training did yield a statistically significant improvement of word recognition skills. The result has pedagogical implications for researchers in the field of second language teaching, instructors, curriculum designers, conductors of interpreting programs for training future interpreters, material producers and all who are involved in language study and pedagogy.